Review of Analytical Approaches for Simulating Motions of Helical Vortex - V. L. Okulov; V. L. Okulov; Y. Fukumoto (Frontiers in Energy Research, 2022)
The study investigates helical vortices, which are fundamental structures in fluid dynamics, and a basic model of tip vortices behind wind turbines. In connection with the intensive development of wind energy, interest in modeling helical vortex wakes behind the rotors has increased. Therefore, the purpose of this mini-review is to compare the existing methods for calculating the induced velocities of screw vortices. The three methods for calculating the motion of helical vortices are compared. Two typical forms of vorticity with uniform (Rankine-type) and Gaussian distributions in the core of helical vortices are compared, and the minimum distance between the vortex filaments or their turns is identified with sufficient accuracy in both cases. The results presented in this mini-review can be used to model the helical vortices in the rotor wakes, central helical vortices in vortex devices, or natural phenomena such as tornadoes, dust tornadoes, and waterspouts.